Kazalniki kakovosti zdravljenja z zdravili z vidika farmacevta - Detiček, Andreja (Farmacevtski vestnik, 2015)
In the healthcare system quality indicators can measure the quality of structures, healthcare processes and treatment outcomes. They are informative for healthcare providers, the payer and the patients. They should be implemented into the system successively starting with the most actual and professionally relevant ones. In Slovenia quality indicators are already in use in the hospitals and primary ambulatory patient care. Among them only few measure the quality of pharmacotherapy. Together with the development of new cognitive pharmacy services, such as medication use review and clinical medication review, their quality should be followed. Many useful examples of the indicators and good databases are available. In the future, pharmacists are challenged to form specific indicators that will reflect the main goals oftheir services, namely the indicators of patient adherence and understanding, appropriate medication use, specific pharmacotherapy indicators that concern various drugs, patient populations and outcomes.
Keywords: kazalniki kakovosti; zdravljenje z zdravili; kognitivne storitve; pregled uporabe zdravil; farmakoterapijski pregled